Magnitude, Trends, and Determinants of Institutional Delivery Among Reproductive Age Women in Kersa Health and Demographic Surveillance System Site, Eastern Ethiopia: A Multilevel Analysis - Temam Beshir Raru; Galana Mamo Ayana; Mohammed Yuya; Bedasa Taye Merga; Mohammed Abdurke Kure; Belay Negash; Abdi Birhanu; Addisu Alemu; Yadeta Dessie; Merga Dheresa (Frontiers Media S.A., 2022)
BackgroundInstitutional delivery service utilization is a critical and proven intervention for reducing maternal and neonatal mortality. Institutional delivery service utilization can improve maternal health and wellbeing by ensuring safe delivery and reducing problems occurring during childbirth. In Ethiopia, almost all previous researches were cross-sectional studies and most of them were based on small sample sizes and there are no sufficient reports for the trends. Therefore, this study aimed to assess the magnitude, trends, and determinants of institutional delivery using surveillance data from the Kersa Health and Demographic Surveillance System (HDSS), in Eastern Ethiopia from 2015 to 2020.MethodsThe study was conducted among reproductive-aged women selected from the Kersa HDSS site, Eastern Ethiopia for the duration of 2015 to 2020. Data were extracted from the Kersa HDSS database system. After coding and recoding, the data was exported to R software for further analysis. A chi-squared test was used for trends to examine the significance of the change. A multilevel logistic regression model was fitted to identify determinants of institutional delivery. An adjusted odds ratio with a 95% confidence interval (CI) was used to measure the strength of the associations. Statistical significance was declared at a p-value < 0.05.ResultsA total of 20,033 reproductive age women were employed for analysis. The overall magnitude of institutional delivery was 45.03% with 95% CI (44.33-45.72). The institutional delivery has shown a decreasing trend over the 6 years' and there is statistical significance for the declining. Semi-urban resident [AOR = 2.33, 95% CI: 1.37-4.48], urban resident [AOR = 7.18, 95% CI: 5.24, 8.71], read and write [AOR = 1.54, 95% CI: 1.18, 2.01], literate [AOR = 1.46, 95% CI: 1.34-1.59], and antenatal care [AOR = 1.73, 95% CI: 1.58-1.88] were significantly associated with institutional delivery.ConclusionThe magnitude of institutional delivery was relatively low and has shown a decreasing trend. Community-based interventions should be strengthened to reverse the decreasing trend of institutional delivery. Targeted information dissemination and communication should be provided to those mothers who have no formal education and attention should be given to rural residents.